Medulloblastoma in a Calf: Case Report - Silva, Rafael J.; Afonso, José Augusto B.; Mendonça, Carla L.; Dantas, Alexandre C.; Guimarães, Janaína A.; Dantas, Antônio F.; Torres, Marcia B. A. M.; Kommers, Glaucia D. (Brazilian Journal of Veterinary Pathology, 2015)
A two-month-old calf was presented to the Bovine Clinic of the Universidade Federal Rural de Pernambuco, Campus Garanhuns (Brazil), with a history of lack of motor coordination in the hind limbs, progressing toward laterally inclined ambulation and imbalance since birth. The recent onset of daily seizures left the calf unable to stand. The animal exhibited pedaling movements and salivation. During the clinical exam, the calf was in lateral recumbency, with hyperextension of the fore and hind limbs, myoclonus, intention tremors (mainly of the head), opisthotonus and nystagmus. The signs were exacerbated upon stimulation. Anus and tail reflexes were diminished. The blood count findings were non-specific. The necropsy revealed a whitish, friable mass with an irregular contour affecting the surface and interior of the cerebellum and brain stem, with the left cerebellar hemisphere more affected. The lateral ventricles (mainly the left ventricle) were dilated and herniation of the cerebellum through the magnum foramen was observed. The diagnosis of medulloblastoma was performed based on the anatomical location and histopathological characteristics of the tumor.